2022
DOI: 10.3390/children9111676
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of Advanced Ultrasonography Imaging Techniques in Infants with Biliary Atresia (BA): A Systematic Review and Meta-Analysis

Abstract: The early diagnosis of biliary atresia (BA) in cholestatic infants is critical to the success of the treatment. Intraoperative cholangiography (IOC), an invasive imaging technique, is the current strategy for the diagnosis of BA. Ultrasonography has advanced over recent years and emerging techniques such as shear wave elastography (SWE) have the potential to improve BA diagnosis. This review sought to evaluate the diagnostic efficacy of advanced ultrasonography techniques in the diagnosis of BA. Six databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
(208 reference statements)
0
2
0
2
Order By: Relevance
“…The study indicated that the cutoffs for predicting advanced fibrosis (≥F3) were 16 kPa (AUC: 0.98; sensitivity: 87.5%; specificity: 96.7%) in BA and 8.7 kPa (AUC: 0.98; sensitivity: 93.8%; specificity: 96.1%) in other chronic liver diseases [33]. A systematic review reported that SWE was an advanced ultrasonography technique that had a good pooled diagnos-tic performance (sensitivity: 83%; specificity: 77%; AUC: 0.896) for liver fibrosis due to BA [34]. An AUC exceeding 0.8 is commonly regarded as a strong indicator of diagnostic performance [35].…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated that the cutoffs for predicting advanced fibrosis (≥F3) were 16 kPa (AUC: 0.98; sensitivity: 87.5%; specificity: 96.7%) in BA and 8.7 kPa (AUC: 0.98; sensitivity: 93.8%; specificity: 96.1%) in other chronic liver diseases [33]. A systematic review reported that SWE was an advanced ultrasonography technique that had a good pooled diagnos-tic performance (sensitivity: 83%; specificity: 77%; AUC: 0.896) for liver fibrosis due to BA [34]. An AUC exceeding 0.8 is commonly regarded as a strong indicator of diagnostic performance [35].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 15 studies (2185 cases) showed higher values of SWE in BA as compared to non-BA. SWE had a sensitivity of 83% and specificity of 77% for differentiating BA from non-BA NC [7]. But we need to remember that non-BA NC is a very heterogenous group, with some etiologies causing early cirrhosis (GALD, PFIC-2), and some not (sepsis, TORCH infections).…”
mentioning
confidence: 99%
“…comentam sobre novas tecnologias como biomarcadores microRna circulantes e sobre a relevância de estudos envolvendo o conjunto de dados de microarray BA GSE46960 associado a outras doenças causadoras de colestase intra-hepática e como a expressão gênica hepática pode ser útil para tratamento clínico Gunda et al (2022). destacam que a AB pode ser diagnosticada utilizando vários métodos de imagem e não deve ser limitado seu diagnostico a presença de sintomas clássicos como icterícia com acolia ou colúria, pois nem sempre podem estar presentes precocemente.…”
unclassified
“…destacam que a AB pode ser diagnosticada utilizando vários métodos de imagem e não deve ser limitado seu diagnostico a presença de sintomas clássicos como icterícia com acolia ou colúria, pois nem sempre podem estar presentes precocemente. Além da experiência clínica do médico não pode ocorrer atrasos na realização de exames de imagem como colangiografia introperatória (COI), colangiografia retrógrada endoscópica (ERC), ultrassonografia do tipo convencional, com 3D/4D, com contraste (CEUS) e a associada com elastografia por onda de cisalhamento (SWE) (Li e Wang, Nos casos duvidosos do diagnóstico de atresia biliar, métodos invasivos devem ser utilizados para identificação de padrão obstrutivo como a biópsia hepática percutânea e a colangiografia intraoperatória, considerada o padrão ouro para o diagnóstico de AB e com maior risco de morbidade segundoGunda et al (2022). Uma vez realizado o diagnóstico, impreterivelmente antes de dois meses de vida do lactente, tem na portoenterostomia hepática de Kasai (KHPE) a principal opção de tratamento cirúrgico com possibilidade de altas taxas de recanalização de ductos biliares e melhora da icterícia protelando em meses há anos a necessidade de transplante hepático(Liu et al,2024) Fligor et al (2022).…”
unclassified